Regional and Social Disparities for Obesity among Austrian Adults: Representative Long-term Trends from 1973–2014 - Großschädl, Franziska; Stronegger, Willibald Julius (Das Gesundheitswesen, 2019)
Study aim To present regional long-term trends for the prevalence of obesity (BMI ≥ 30 kg/m²) among Austrian adults in Western, Central and Eastern Austria. Furthermore, the educational inequality regarding obesity was analysed in these regions in Austria for the investigation period.Methods Self-reported data from six nationally representative, cross-sectional surveys (n=194,030) conducted between 1973 and 2014 were analysed. Absolute changes (AC) and Etiologic fractions (EF) were calculated to measure trends. The extent of social inequality was presented by the relative index of inequality (RII) based on the educational level.Results Since 1973, a clear east to west gradient for obesity among adults in Austria has been observed. In 2014, the age-standardized prevalence was highest among Eastern Austrian adults (women: 16.9%; men: 18.2%). A constant increase in obesity among men has been visible since 1983. Since 2007, the values for women have stabilized, while the prevalence of obesity among female Austrians in Western and Central Austria decreased. Considering the AC for the prevalence of obesity from 1983 on, the highest increase was found among women (+2.60%) and men (+1.56%) in Eastern Austria. The outcomes regarding social inequality are instable on a regional level, with the highest RII observed in 2014 for Central Austria.Conclusion These study findings reveal significant regional differences in the prevalence of obesity in Austria and confirm the existence of an current east-west gradient in Austria for obesity. Considering the latest trends, especially men represent a risk group for obesity in the 3 regions.
Keywords: obesity; Body Mass Index; Austria; regional trends; social inequality